2013
DOI: 10.1016/j.mcm.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Almost sure exponential stability of solutions to highly nonlinear neutral stochastic differential equations with time-dependent delay and the Euler–Maruyama approximation

Abstract: a b s t r a c tThis paper may be considered as a natural sequel to the paper [M. Milošević, Highly nonlinear neutral stochastic differential equations with time-dependent delay and the Euler-Maruyama method, Mathematical and Computer Modelling 54 (2011) 2235-2251]. In the present paper, global almost sure (a.s.) asymptotic exponential stability of the equilibrium solution for a class of neutral stochastic differential equations with timedependent delay is considered, under nonlinear growth conditions. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 14 publications
1
27
0
Order By: Relevance
“…On the basis of the papers [12] and [13], one can conclude that hypotheses A 2 − A 4 , together with the local Lipschitz condition on f and and the assumption (8), guarantee the existence and uniqueness of the global solution of Eq. 1, which is almost surely exponentially stable.…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the papers [12] and [13], one can conclude that hypotheses A 2 − A 4 , together with the local Lipschitz condition on f and and the assumption (8), guarantee the existence and uniqueness of the global solution of Eq. 1, which is almost surely exponentially stable.…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%
“…1, which is almost surely exponentially stable. Results from [13] suggested to employ A 4 , as well as the linear growth condition A 1 on the drift coefficient of Eq. 1, in order to prove the almost sure exponential stability of the θ-Euler-Maruyama solution.…”
Section: Introduction and Preliminary Resultsmentioning
confidence: 99%
“…[15,16,20,21,17]. However, as far as we know, there are few results on the exponential stability of the θ -EM approximations of NSDDEswMS except [22]. In [22], Milošević only presented sufficient conditions of the exponential stability property for the Euler-Maruyama equilibrium solution of the given NSDDEswMS.…”
Section: Introductionmentioning
confidence: 99%
“…Note that θ -EM includes the classical EM method (θ = 0), the backward EM method (θ = 1) and the so-called trapezoidal method (θ = 1 2 ). In [22], the author needed the linear growth condition on both f and g for the almost sure exponential stability for the special case of (1.5) and (1.6) (θ = 0).…”
Section: Introductionmentioning
confidence: 99%
“…However, the study on stability of numerical method for neutral stochastic differential systems is relatively scarce due to their technical difficulties, which is the main topic of the present paper. Recently, Milošević [14] showed that almost sure exponential stability of solutions to highly nonlinear neutral stochastic differential equations with time-dependent delay. To the best knowledge of authors, there is no work on the stability of numerical solution to NSFDE.…”
Section: Introductionmentioning
confidence: 99%